RISK FACTORS IDENTIFICATION FOR AGGRESSIVE BEHAVIOR AND PROTECTIVE RESOURCES OF MINORS IN THE MANAGERIAL-SUPERVISORY MODEL OF THE COURT TUTORAGE IN POLAND - Andrzej Węgliński (Probacja)
The article presents various views on managerial-supervisory strategies in probation work. On the basis of cross-sectional studies was made analyzes risk factors and protection resources of juveniles supervised by probation officers. Recognized risk factors enable profiling of supervised persons and individualized treatment of minors and supporting them in the process of social rehabilitation. The classification of minors into risk groups is aimed at improving the efficiency of the work of family probation officers and increasing the sense of security in society.